3.2-Å-resolution structure of the 90S preribosome before A1 pre-rRNA cleavage - Cheng, Jingdong; Kellner, Nikola; Hurt, Ed (Nature structural & molecular biology, 2017)
The 40S small ribosomal subunit is cotranscriptionally assembled in the nucleolus as part of a large chaperone complex called the 90S preribosome or small-subunit processome. Here, we present the 3.2-Å-resolution structure of the Chaetomium thermophilum 90S preribosome, which allowed us to build atomic structures for 34 assembly factors, including the Mpp10 complex, Bms1, Utp14 and Utp18, and the complete U3 small nucleolar ribonucleoprotein. Moreover, we visualized the U3 RNA heteroduplexes with a 5′ external transcribed spacer (5′ ETS) and pre-18S RNA, and their stabilization by 90S factors. Overall, the structure explains how a highly intertwined network of assembly factors and pre-rRNA guide the sequential, independent folding of the individual pre-40S domains while the RNA regions forming the 40S active sites are kept immature. Finally, by identifying the unprocessed A1 cleavage site and the nearby Utp24 endonuclease, we suggest a proofreading model for regulated 5′-ETS separation and 90S-pre-40S transition.